1994
DOI: 10.1007/bf00201664
|View full text |Cite
|
Sign up to set email alerts
|

Differential ultrastructural aberrations of collagen fibrils in Ehlers-Danlos syndrome types I?IV as a means of diagnostics and classification

Abstract: Among the different subtypes of Ehlers-Danlos syndrome (EDS), the dominant types I-III have, so far, been uninformative biochemically and molecular genetically, and diagnostic problems with subgroup boundaries often arise. We have investigated the ultrastructural pattern of connective tissue macromolecules in skin biopsy specimens of some 85 patients aged 4 months-54 years who exhibit clinical symptoms or the suspicion of EDS I-IV. Based on the differential features of collagen fibrils and ground substance mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
10

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 29 publications
7
106
0
10
Order By: Relevance
“…A "cauliflower" deformity of collagen fibrils is characteristic. 48 However, these findings are not specific for EDS and, therefore, not diagnostic. Furthermore, ultrastructural changes, usually most pronounced in the central parts of the reticular dermis, may be missed if the skin biopsy is not of full thickness.…”
Section: Ultrastructural Studiesmentioning
confidence: 94%
“…A "cauliflower" deformity of collagen fibrils is characteristic. 48 However, these findings are not specific for EDS and, therefore, not diagnostic. Furthermore, ultrastructural changes, usually most pronounced in the central parts of the reticular dermis, may be missed if the skin biopsy is not of full thickness.…”
Section: Ultrastructural Studiesmentioning
confidence: 94%
“…The most common reported molecular mechanism in classic EDS is the functional loss of one COL5A1 allele (Schwarze et al, 2000;Wenstrup et al, 2000), with a haplo-insufficiency for collagen V. Abnormal fibril formation is seen in the classic EDS and the dermis of EDS patients contains large, irregular collagen fibrils (Hausser and Anton-Lamprecht, 1994;Vogel et al, 1979). Studies using fibroblasts from EDS patients with characterized mutations in COL5A1 and a mouse Col5a1 +/2 model of classic EDS have demonstrated that heterotypic collagen I and V interactions are involved in the regulation of fibril diameter and fibril number (Segev et al, 2006;Wenstrup et al, 2004a;Wenstrup et al, 2004b;Wenstrup et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The skin biopsies of all four twin brothers did not show any severe connective tissue abnormalities. 5 The figure, A, shows the structurally intact arterial wall of the STA of a control subject (control C2 4 ). Vascular smooth muscle cells (SMC) were of the physiologic contractile phenotype and neither fresh nor degraded erythrocytes or other cellular debris were found.…”
Section: Two Sets Of Identical Twins With Cervical Artery Dissection mentioning
confidence: 99%